1975
DOI: 10.3168/jds.s0022-0302(75)84785-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Toxicity of Cadmium, Mercury, and Lead in Animals: A Review

Abstract: Cadmium, mercury, and lead are toxic to humans and animals. Although cadmium and inorganic mercury toxicities occur in humans, they have not been observed in domestic livestock under practical conditions. In contrast, cattle, especially young calves, are extremely susceptible to lead toxicity. Apparently, cattle are more tolerant of cadmium than are other animal species. Due partially to higher absorption and longer retention times in the body, the alkyl mercuries, especially methyl mercury, are more toxic tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
3

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(66 citation statements)
references
References 69 publications
5
57
1
3
Order By: Relevance
“…Comparable values were reported by Drapal et al (1997) who found values of 2 to 10 Jlg-kg ol , 11 to 50 Jlg-kg-I , and 100 to 300 Jlg-kg-I in 85.7%, 13.6%, and 0.7% of adult cattle, respectively. Our results have confirmed the finding of Neathery and Miller (1975) that muscular tissue, representing a major part of body mass, is well protected against cumulation of cadmium and that its concentration is not age-dependent unless the intake is markedly increased. Underwood (1977) observed a marked increase in the concentration of cadmium in muscles only when the diet contained 450 ppm Cd.…”
Section: Cows Heifers Bulls Calvessupporting
confidence: 80%
“…Comparable values were reported by Drapal et al (1997) who found values of 2 to 10 Jlg-kg ol , 11 to 50 Jlg-kg-I , and 100 to 300 Jlg-kg-I in 85.7%, 13.6%, and 0.7% of adult cattle, respectively. Our results have confirmed the finding of Neathery and Miller (1975) that muscular tissue, representing a major part of body mass, is well protected against cumulation of cadmium and that its concentration is not age-dependent unless the intake is markedly increased. Underwood (1977) observed a marked increase in the concentration of cadmium in muscles only when the diet contained 450 ppm Cd.…”
Section: Cows Heifers Bulls Calvessupporting
confidence: 80%
“…Our results on levels of gastrointestinal absorption are consistent with levels reported in various vertebrate experiments ranging from 0.5 to 16% (Neathery and Miller 1975;Xu andWang 2002, Hispard et al 2008;Mann et al 2006;Zalups and Ahmad 2003) according to the Cd-concentration in diet that individuals were fed. In our study, the proportional accumulation in liver and kidney depended on the amount of Cd ingested with decreasing assimilation efficiency when ingestion increased, suggesting that as the dose of Cd increases, assimilation decreases.…”
Section: Discussionsupporting
confidence: 80%
“…In the limited observations in humans and in animal experiments, the average absorption of Cd from the gastrointestinal tract has been estimated as 1%-8% of the Cd that enters the mucosa from the lumen and actually passes into the body [7][8][9][10][11][12][13] . Factors affecting the absorption and tissue distribution of ingested Cd include the animal species, the chemical form of Cd, the dose, the duration, the age of the animal, and interactions of Cd with various nutrients 1-6, 14, 15) .…”
Section: Introductionmentioning
confidence: 99%